Human Judgment in AI-Assisted Accounting Decision-Making - Devina Agustin; Yusnaini . (CV. ITTC INDONESIA, 2026)
The accounting profession is increasingly integrating artificial intelligence to support decision-making, yet human judgment remains an irreplaceable core element. AI enables big data processing, anomaly detection, and rapid, accurate estimation recommendations, while human accountants are responsible for interpreting business context, assessing risk, and considering ethical and behavioral factors. This systematic review analyzes how such collaboration affects the quality of human judgment in accounting decision-making. A synthesis of 8 Scopus-indexed articles published between 2022 and 2025 indicates that AI enhances efficiency, accuracy, and risk detection capabilities, but also poses risks of over-reliance, reduced professional skepticism, and a shift in the accountant’s identity if human oversight is weak. Optimal strategies include continuous training, educational reform, and strict AI governance to ensure that human judgment remains robust and ethical. The literature is still dominated by contexts from developed countries, so empirical research in Indonesia is needed to ensure that approaches are better suited to the behavioral characteristics and regulations of local accountants.